Translation and adaptation of columbia card task and affective and deliberative aspects of decision-making during development and crack use - Schiavon, Bruno Kluwe (2015)
Making adaptive decisions requires weighing risks and benefits and the ability to learn about an ever-changing environment. Ordinary choices ca be influenced by contextual factors (e.g., feedback exposure, affective- or deliberative-based scenarios) and individual factors (e.g., developmental stages and psychopathologies). Particularly, two specific conditions regarding developmental stages and psychopathologies have been extensively related to alterations in decision-making processes and consequently increased risk-taking behaviors: adolescence and drug addiction. Cocaine dependence has been related with poor decision-making, since continuous drug abuse shifts from controlled drug use (decreasing deliberative inhibitory control) to compulsive drug use (increasing the reward sensitization)—the dual-processing perspective—which opens a vulnerability window for risk-taking behaviors. Adolescence is a natural developmental period marked by risk-taking behavior, in which different developmental trajectories of brain regions involved in reward motivation and control processes may lead to adolescents’ increased risktaking. Although efforts have been made to elucidate how the dysregulation of cognitive control and of the reward-affective system leads to risk behavior in drug addiction and adolescents, it has been mostly performed separately. Objectives. The present dissertation aimed to (1) adapt the Columbia Card Task (CCT) to Brazilian Portuguese and (2) investigate the relation of contextual factors (affective- and deliberative-based contexts) and individual factors (drug addiction and adolescence) in decision-making processes (i.e., risk-taking behavior and information use). To achieve this goal, this dissertation is composed of two studies. Methods: To translate and adapt the CCT we followed standardized guidelines and performed a pilot study with 29 university students. In the second study, we compare the role of feedback and the use of explicit information in risk-taking (affective process) and information use (deliberative process) in 27 female crack cocaine users (CU) and 18 female adolescents (AD) in comparison to 20 female adult controls (CG). Results. The first study showed that CCT was adequately adapted to Brazilian Portuguese. The pilot study suggests that manipulation of feedback among CCT conditions had an effect on the risk-taking index and information use. The second study showed that CU showed a lack of information use on both CCT conditions, despite the fact that during the delayed-feedback condition, CU did not differ from CG on risk-taking behavior. Adolescents mostly used the “probability” information; notwithstanding, they did not modulate their responses, making riskier choices in both delayed- and no-feedback conditions when compared to CG. Conclusions. Together, our results suggest that the Brazilian version of CCT performs well and is a versatile method for the assessment of affective and deliberative decision-making under risk according to different feedback manipulation scenarios. Moreover, the feedback plays a different role in the decision-making of female crack cocaine users and female adolescents.